Conversar e tensionar na formação (des)continuada inventiva/inclusiva : cartografia de uma escola-território - Cuevas, Marcia Roxana Cruces (2015)
The thesis begins with questions about the training of inclusive educators from the network paradigm. The conception of man and the of world which guides this investigation indicates the complexity of life, understanding man and society as enmeshed in a network of productions, intensities of meanings and affectations which constitute reality. Understanding the phenomena as collective production, production of subjectivity, where the standards which are are assumed as normal are the fruit of a complex process of reproduction of subjects and the reinvention of life through the power of creativity. The work is configured as a mobile qualitative research, where we inquired and asked questions about how the training of teachers is effective as a from of resistance to the creation of capitalist subjectivity? How the discussions about teacher training actualised and invented inclusive modes of existence? We carried out a research-intervention because it assumes the plan of experience as an intervention. We groped, we fabricated productive devices in order to make knowledge emerge from doing. We carried out a cartography of actions and creations of professionals of a public school providing elementary education for children and adults, working in three shifts with people from the lower classes and who were denied the right to study. We monitored the training paths of a group of teachers from the territory-school throughout 2014. All of the reports and narratives were registered in the field diary and recorded digitally. The material produced was analysed from the discursive analytical guidelines proposed by Foucault, seeking to escape from the fragile interpretation of what would be behind the documents, because we understand the productions are a historical and political achievement. The discursive analysis led us to two plateaus, two regions, intensive territories: a) The discontinued training which streamlines the organisational process of teaching, and b) Inclusive practice via the production of collaborative networks which streamlines the school-territory. Training in challenging times demands to be inventive. We saw in the experiences together with the school-territory, that when training is governed by implication analysis, where there is no linearity of study and reflection, since each meeting converses about new experiences and problems to be faced, collaborative networks proliferate which are fundamental for overcoming individualism. Training which operates through resistance will produce ethical/aesthetical/ political assemblages and connections enabling the production of other values which are different from neo-liberal society, because it strengthens the collectivisation of life, creating territorial social networks. The meeting of educational modalities for youth, adult education and special needs education via inventive/discontinued/ethical/aesthetical/political training presents itself as a strong path and mode of production for an equitable education to be both public and popular